A study on heat transfer in seasonal snow pack (MAUSAM, 1981)
Two sample of stratigraphic observations of snow cover recorded at Kanzalwan (34 deg. 35' N, 74 deg. 40' E, 2410 m) during winters of 1977 to 1979 have been analysed with the aim to bring out (i) variations of snow surface temperatures and its correlation with the temperature of ambient au, (ii) march of temperature with time and depth of snow pack, (III) the diurnal variations of snow temperatures in various layers of the snow cover, and (iv) the cold content of the seasonal snow cover and its temporal variations.